Multidimensional polarization of income and wealth: The extent and intensity of poverty and affluence - Bettina Scherg (Leuphana Universität Lüneburg, Forschungsinstitut Freie Berufe (FFB), 2014)
Income and wealth are important determinants of individual economic well-being because they are a fundamental resource for consumption. Due to increasing inequality the distribution of income and wealth has moved more and more into the focus of scientific and political attention. The aim of this paper is to determine the extent and the intensity of multidimensional polarization of both income and wealth. Individual well-being is modeled by a well-being function directly affected by income and wealth. In order to have a flexible functional form for the well-being function the translog function is chosen. The parameters of the well-being function are not chosen arbitrarily but determined by the German population. From the perspective of an interdependent relation of the polarization dimensions income and wealth, the extent of multidimensional poverty and affluence is represented by the number of people who are assigned to be multidimensionally poor or affluent. The polarization intensity is measured by the multidimensional mean minimum polarization gap (2DGAP). This polarization intensity measure provides a transparent representation of each singular attribute and account for their possible interdependent relations. The data basis for the empirical investigation is the SAVE study from 2010 for Germany. – – Einkommen und Vermögen leisten einen wichtigen Beitrag zur individuellen ökonomischen Wohlfahrt, da sie eine wichtige Grundlagen für den Konsum von Gütern sind. Aufgrund einer zunehmenden Ungleichheit ist die Verteilung von Einkommen und Vermögen privater Haushalte in den letzten Jahren in der Bundesrepublik Deutschland zunehmend in das Zentrum der wissenschaftlichen und politischen Aufmerksamkeit gerückt. Das Ziel dieser Arbeit ist, das Ausmaß und die Intensität der Polarisation von Einkommen und Vermögen zu bestimmen. Die individuelle Wohlfahrt wird von einer Wohlfahrtsfunktion modelliert, die direkt von Einkommen und Vermögen abhängt. Für eine möglichst flexible funktionale Form der Wohlfahrtsfunktion wurde die Translog Funktion gewählt. Die Parameter der Wohlfahrtsfunktion werden nicht willkürlich gewählt, sondern anhand der deutschen Bevölkerung bestimmt. Unter der Perspektive einer interdependenten Betrachtung wird das Ausmaß der multidimensionalen Polarisierung über die Anzahl der Personen in den Polen belegt. Die Polarisationsintensität wird über den Mean Minimum Polarization Gap (2DGAP) gemessen. Dieses Maß der Polarisierungsintensität berücksichtigt transparent jede einzelne Dimension und erlaubt gleichzeitig eine interdependente Betrachtung beider Dimensionen. Als Datengrundlage für die empirische Untersuchung wird die SAVE-Studie von 2010 für Deutschland verwendet.
Keywords: I32; D31; J22; 330; multidimensional polarization; polarization intensity; income; wealth; poverty; affluence; translog well-being function; Minimum Multidimensional Polarization Gap (2DGAP); Multidimensionale Polarisierung; Polarisierungsintensität; Einkommen; Vermögen; Armut; Reichtum; Translog-Nutzenfunktion; CES Nutzenfunktion